15.4: Weight Optimization of Near‐Eye Light Field Displays Based on Human Visual System. Issue 1 (June 2015) - Ding, Jun; Zhong, Qing; Liu, Mali; Li, Haifeng; Liu, Xu
Abstract : According to human visual system, we utilize human eyes' central vision to design the weight matrix, which indicates perceptual significance of the rays, making optimization results closer to ground truth. In our design, we employ multiple LCD layers to optimize near‐eye displays, allowing both vertical and horizontal parallax.